Kelayakan LKPD berbasis PBL disertai KPS pada Materi Perubahan Lingkungan Kelas X: Kelayakan LKPD Berbasis PBL disertai KPS Pada Materi Perubahan Lingkungan Kelas X - Dewi Portuna Suwanda; Wahyuni , Eko Sri; Yuniarti, Anisyah (Journal of Biology Learning, 2024)
The change in the Merdeka Curriculum has made learning tools in various subjects including biology in class X inadequate. This study aims to determine the feasibility of Problem-Based Learning (PBL) based LKPD (student worksheet) accompanied by Science Process Skills (KPS) on the material of environmental changes in class X. The development model refers to the research and development (R&D) method with 5 stages. The stages are potential and problems, data collection, product design, design validation, and design revision. The research instruments used were instrument validation questionnaires and validation sheet questionnaires. The validated aspects are the format, content, language, and benefits/usability of LKPD. Validation was carried out by 5 validators. Analysis of validation results using face validity Aiken's V with criteria V = 0.87. The results showed that the LKPD met the valid criteria with a total average of 0.947. It can be concluded that problem-based learning-based LKPD accompanied by science process skills is declared valid and ready to proceed to the trial stage.